1993
DOI: 10.7326/0003-4819-118-3-199302010-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Asymptomatic Hepatitis B Surface Antigen Carriers

Abstract: Italian HBsAg carriers with initially normal liver function tests have an excellent prognosis: Delta superinfection is infrequent and the risk for developing hepatocellular carcinoma is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
161
0
8

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(173 citation statements)
references
References 0 publications
4
161
0
8
Order By: Relevance
“…Six subjects belonged to a previously well characterized study group of chronic healthy HBsAg carriers with normal liver histology and inhibited HBV replication. 3,4,6 All HBsAg-positive subjects were negative for hepatitis B e antigen (HBeAg) and positive for the corresponding antibody (anti-HBe), as usually observed in chronic HBsAg carriers in our geographic area. 21,22 In both HDV-infected patients and healthy HBsAg carriers circulating HBV genomes could be detected by polymerase chain reaction (PCR) amplification performed following previously described methods.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six subjects belonged to a previously well characterized study group of chronic healthy HBsAg carriers with normal liver histology and inhibited HBV replication. 3,4,6 All HBsAg-positive subjects were negative for hepatitis B e antigen (HBeAg) and positive for the corresponding antibody (anti-HBe), as usually observed in chronic HBsAg carriers in our geographic area. 21,22 In both HDV-infected patients and healthy HBsAg carriers circulating HBV genomes could be detected by polymerase chain reaction (PCR) amplification performed following previously described methods.…”
Section: Patientsmentioning
confidence: 99%
“…Consequently, HBsAg-positive patients with suppressed viral replication and undetectable levels of viremia have usually low grade or absence of hepatocellular injury. [2][3][4] Nevertheless, several observations suggest that an undefined amount of free viral genomes may persist into the hepatocytes of these subjects, 5,6 and such episomal HBV forms might be implicated in the reactivation of silent infections that may occur either spontaneously [7][8][9] or in conditions of immunosuppression, [10][11][12] or, in patients treated with antiviral drugs, after stopping therapy. [13][14][15][16][17] Thus, analysis and quantification of intrahepatic HBV genomes appear to be of biological interest and may provide useful clinical information.…”
mentioning
confidence: 99%
“…15,41 Very little longitudinal data is available on the latter patients, but liver disease is generally present in patients with high HBV DNA levels. 30,32,42 Among adults in Asia and the Oceania with elevated ALT levels and carriers of all ages with childhood or adult-acquired HBV infection, the rate of clearance of HBeAg averages between 8% and 12% per year. [29][30][31][32][33]43 The rate of clearance of HBeAg is much lower in Asian children (most of whom have normal ALT levels) 34,35 and in immunocompromised subjects.…”
Section: Terminology and Natural History Of Chronic Hbv Infectionmentioning
confidence: 99%
“…53 Other European and US studies based upon HBV carriers have confirmed this results. [54][55][56][57][58] In our study, it is reasonable to expect a low number of subjects with liver disease at entry of the cohort, because all subjects were screened volunteer blood donors. In fact, the risk of death from liver disease in our cohort was higher in the second decade of follow-up than in the first, suggesting that most of the HBV carriers were healthy at the entry of the cohort.…”
mentioning
confidence: 99%